MENEROPONG "KOMUNIKASI BEBAS PENINDASAN" Buah Pemikiran Kritis Jurgen Habermas dalam Realitas Wajah Pertelevisian Indonesia (Dilihat dari Ontologis, Epistemologis, Aksiologis Kajian Media) - S.Luhukay, Marsefio (Scriptura, 2007)
Critical Theory that was built by Jurgen Habermas strove to find a methodology to uncover the other way around%2C namely relatedness between knowledge and human interests as social creatures. Therefore%2C critical theory of Jurgen Habermas was often called Critical Theory of Ideology; since there was an inevitable correlation between knowledge and social praxis%2C between knowledge%2C technology and issues of modern societies such as alienation%2C technological domination%2C reification%2C social repression%2C dehumanization%2C depersonalization and various agonies and depression of human beings due to intervention and penetration of knowledge and technology. Such was the case that ideological critics intended to reveal negative intentions disguised by ideology derived from distorted communication models systematically that led to social injustice and suppression. Abstract in Bahasa Indonesia : critical theory%2C social praxis